Barreiro López, Paula. Cold Atlantic. Transactional stories of art and politics in the times of the iron curtain. Madrid: Brumaria, 2019, 560 p - Moriente Díaz, David (Universidad Pedagógica y Tecnológica de Colombia, 2019)
Review